O nome e o lugar: a toponímia na região central de Minas Gerais - Joviano Goncalves dos Santos (2012)
This research aims to study place names in the central Minas Gerais municipalities of Augusto de Lima, Cordisburgo, Curvelo, Felixlândia, Inimutaba and Morro da Graça, around Corinto, which is considered the center of the state of Minas Gerais. This area of the state is known for its great development, due to the presence of numerous farms, coming fromPortugal, São Paulo, Bahia among others in the eighteenth and nineteenth century. The theoretical and methodological framework is based on Dick (1980, 1990a, 1999) and related work, with adaptations. The place names analyzed were collected from the speech ofinformants of this area. The twenty eight interviews have been recorded, both in urban and rural areas and afterwards transcribed. Due to the spoken language characteristics of the data collected, some observations have been made on the mechanisms of nomination and itspredicative nature. The analysis of one hundred thirty-six place names showed that nature and its typical local elements are intrinsically related to the majority of them, which are physical in nature. The antropocultural nature are also reflected in place names, but not overwhelmingly. A division between simple and compound taxonomy has been proposed so as the most productive lexical bases for the formation of place names in the mesocentral area of Minas Gerais. The results showed that the majority of place names in the area are of hydrotoponyms being the physical nature their main motivation, the same being true of thephytoponyms. The antropocultural feature has proved to be relevant for the anthropo-, socioand hagiotoponyms. The current place names have been the starting point for searching into a past motivation for their creation and have revealed many traces of cultural aspects, throughits history. Most place names have their origin in the Portuguese language, and a minority of them have an Indigenous and African origin.